Apremilast generic for the treatment of active psoriatic arthritis: A single-center real-life experience from India - Sanjiv Amin; Aneesa Kapadia; Dhiraj Dhoot; Hanmant Barkate (Indian Journal of Rheumatology)
Introduction: Apremilast has been recently introduced in the treatment of adult psoriatic arthritis (PsA) patients in India. Its efficacy and safety have been established in the landmark clinical trials; however, there is still a dearth of its real-world experience in the management of PsA in India. Materials and Methods: A retrospective cohort analysis of electronic medical records was conducted at our clinic, to study the effectiveness and tolerability of apremilast 30 mg twice a day in the management of PsA. A total of 86 patients were included in this report. Patients were classified as responders and nonresponders based on the overall physician judgment of clinical status, especially improvement of symptoms as per the disease activity in PsA (DAPSA) criteria. Results: Of the 86 patients started on apremilast, 44 patients had at least 16 weeks of follow-up assessment. Of these 44 patients, 39 were of peripheral arthritis and five were of axial spondyloarthritis. Twenty-five of 39 (64%) patients were classified as responders and 14 (36%) as nonresponders based on the DAPSA criteria. On analyzing the DAPSA scores at baseline and subsequent follow-up, there was statistically significant improvement in mean DAPSA score. Remission was seen in three patients (7.7%) and low disease activity in 16 (41%) patients at 16 weeks. Only six patients developed one or more side effects. The most common side effects were gastrointestinal symptoms. Conclusion: These results, from a real-world setting in India, confirm the effectiveness and tolerability of apremilast in PsA as seen in clinical trials.